2013
DOI: 10.1371/journal.pone.0066107
|View full text |Cite
|
Sign up to set email alerts
|

Augmented BMPRIA-Mediated BMP Signaling in Cranial Neural Crest Lineage Leads to Cleft Palate Formation and Delayed Tooth Differentiation

Abstract: The importance of BMP receptor Ia (BMPRIa) mediated signaling in the development of craniofacial organs, including the tooth and palate, has been well illuminated in several mouse models of loss of function, and by its mutations associated with juvenile polyposis syndrome and facial defects in humans. In this study, we took a gain-of-function approach to further address the role of BMPR-IA-mediated signaling in the mesenchymal compartment during tooth and palate development. We generated transgenic mice expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
47
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 51 publications
1
47
0
Order By: Relevance
“…We have shown previously that elevated BMP signaling, either by inactivating Noggin or by forced expression of a constitutively active form of BMPRIa ( BmprIa ) in CNC lineage or in epithelium, disrupts normal development of the palate and tooth (He et al, 2010; Li et al, 2013). To further investigate the potential role of BMP signaling in craniofacial morphogenesis, we generated pMes-Bmp4 conditional transgenic mice.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have shown previously that elevated BMP signaling, either by inactivating Noggin or by forced expression of a constitutively active form of BMPRIa ( BmprIa ) in CNC lineage or in epithelium, disrupts normal development of the palate and tooth (He et al, 2010; Li et al, 2013). To further investigate the potential role of BMP signaling in craniofacial morphogenesis, we generated pMes-Bmp4 conditional transgenic mice.…”
Section: Resultsmentioning
confidence: 99%
“…Among these type I receptors, BmprIa has been shown to play an essential role in craniofacial development (Li et al, 2011; Li et al, 2013; Liu et al, 2005). Since Wnt1Cre -driven expression of a constitutively active form of BMPR-IB ( caBmprIb ) did not produce any visible phenotype in mice (Li et al, 2011), we reevaluated craniofacial phenotype of mice expressing caBmprIa in CNC lineage ( Wnt1Cre;pMes-caBmprIa ) mice and confirmed a lack of syngnathia-like phenotype in these mice (data not shown). Histological analysis also confirmed the origin of palatal shelves, although dramatically deformed, from the maxillary region in Wnt1Cre;pMes-caBmprIa mice (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Mouse genetic manipulation studies have revealed a requirement for precise regulation of BMP signaling in craniofacial development (Bonilla-Claudio et al, 2012; Li et al, 2013; Wang et al, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…We have shown previously that the expression of caBmprIa in CNC lineage induces ectopic activation of Smad1/5/8 signaling as well as p38 signaling in the developing palatal shelves [51]. We therefore set to examine alterations in BMP canonical and non-canonical signaling pathways in the condylar cartilage of Wnt1-Cre;pMes-caBmprIa mice by immunohistochemistry.…”
Section: Resultsmentioning
confidence: 99%